IMPLEMENTASI PROGRAM ECOPRENEURSHIP PADA SISWA ATTENTION DEFICIT HYPER ACTIVITY DISORDER (ADHD) DI SEKOLAH DASAR INKLUSIF - Aryanto, Sani; Junaidi, Febi; Hartati, Tatat; Rahman, Rahman (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
This research was conducted to describe the implementation of the ecopreneurship program in ADHD students including the characteristics, approach/method, parties involved, the impact, and the obstacles of implementation of ecopreneurship program in ADHD students in Inclusive Elementary School. This research uses a qualitative approach with a case study method conducted at SDN Cibabat Mandiri 2 Kota Cimahi. The subject of this study was ADHD students as the primary informant supported by secondary data from orthopedagog, classroom teachers, and extracurricular teachers. Based on the results of the research that has been done, it can be known that ADHD students have very active characteristics and tend to be impulsive when participating in ecopreneur ship programs, but the assisted learning approach through scaffolding method is the key to the teacher's success in directing ADHD students to stay focused on the ecopreneurship program. The implementation of ecopreneurship's program has 3 main impacts on the development of ADHD students, including (1) Internalization of ecopreneurship values; (2) improvement of life skills; and (3) the creation of social interactions as an effort to improve the competence of ADHD students. The results of this study are new findings and can be used as a reference for Inclusive Elementary School in providing an overview of the internalization of ecopreneurship values in ADHD students as a reference for teachers or orthopedagog in developing innovative environmentally based learning patterns in ADHD students in Inclusive Elementary School.Â